2022
DOI: 10.1371/journal.pone.0263903
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary clinical and economic outcomes among oral anticoagulant treated and untreated elderly patients with atrial fibrillation: Insights from the United States Medicare database

Abstract: Background Oral anticoagulants (OACs) mitigate the risk of stroke in atrial fibrillation (AF) patients. Objective Elderly AF patients who were treated with OACs (apixaban, dabigatran, edoxaban, rivaroxaban, or warfarin) were compared against AF patients who were not treated with OACs with respect to their clinical and economic outcomes. Methods Newly diagnosed AF patients were identified between January 2013 and December 2017 in the Medicare database. Evidence of an OAC treatment claim on or after the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Our findings indicate a larger increase in OAC-mediated bleeding risk, despite a lower mean age and lighter comorbidity burden compared to the American cohort. The percentage of AF-patients treated with OAC in the American cohort was low (41 %) compared to the current study (87.1%), and yet the registry reported a significantly lower all-cause and inpatient medical cost for OAC-treated AF patients compared to their non-treated cohort 23 . With the expected surge in AF prevalence 3,24,25 this underlines that a suited screening strategy is needed to identify and treat AF to mitigate mortality, morbidity and health care expenses 26,27 .…”
Section: Bleeding Ratescontrasting
confidence: 78%
See 3 more Smart Citations
“…Our findings indicate a larger increase in OAC-mediated bleeding risk, despite a lower mean age and lighter comorbidity burden compared to the American cohort. The percentage of AF-patients treated with OAC in the American cohort was low (41 %) compared to the current study (87.1%), and yet the registry reported a significantly lower all-cause and inpatient medical cost for OAC-treated AF patients compared to their non-treated cohort 23 . With the expected surge in AF prevalence 3,24,25 this underlines that a suited screening strategy is needed to identify and treat AF to mitigate mortality, morbidity and health care expenses 26,27 .…”
Section: Bleeding Ratescontrasting
confidence: 78%
“… 21 22 An American observational study used OAC as a time-dependent exposure in an older AF population and found an increased risk of major bleeding after OAC initiation (HR: 1.57; 95%CI: 1.54–1.59). 23 Our findings indicate a larger increase in OAC-mediated bleeding risk, despite a lower mean age and lighter comorbidity burden compared with the American cohort. The percentage of AF patients treated with OAC in the American cohort was low (41%) compared with the current study (87.1%), and yet the registry reported a significantly lower all-cause and inpatient medical cost for OAC-treated AF patients compared with their nontreated cohort.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Older age, female sex, and Black race were factors associated with OAC nonuse. 2 The news was slightly better in the Veterans Health Administration (VHA), 3 where OAC nonuse increased from 52% to 65.1% of eligible patients with AF between 2014 and 2018. Patients from racial and ethnic minority groups were less likely to receive OAC than their White counterparts.…”
mentioning
confidence: 99%